Chega de saudosismo: a tradição musical brasileira, o riso e a paródia performatizados pela Tropicália (1967-1970) - Bruzadelli, Victor Creti (2016)
The tropicalismo has been studied by a number of researchers from various fields - history, music, sociology, philosophy, linguistics, among others - who have studied their goals, their aesthetic conceptions, analysis of some songs, their ways of composing and performing songs and their political linkages, etc. Although this movement has been intensely debated and studied, a factor that has not had its due importance revealed by researchers is the tropicalista “laugh” - and this is precisely the focus of this work. This “laugh” is the result of many elements, from costumes, "happenings", dances, generation shock and reality, vocal performances and so on. For this work was chosen “laugh” coming from the “parody process” of musical tradition by tropicalistas musicians. This parody is marked by some unique features that are only possible to realize if we analyze the vocal performance of these musicians-performers, extracting the most information possible from the specificity of their chant. Thus, this work aims precisely include in the context of Tropicália, the Brazilian musical tradition, to parody, to “laugh” and vocal performance. Making possible therefore, another key analysis of this national aesthetic movement present at the end of the 1960s, which is key to the formation of the musical consciousness of Brazil.